PERANAN PUSKESMAS RAWAT INAP SIDOMULYO DALAM PELAYANAN KESEHATAN MASYARAKAT DI KECAMATAN TAMPAN KOTA PEKANBARU - Atik Kartika Sari; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Health is one of the basic human needs, because only in a state of health people can live, grow, work and creativity well. There fore every individual, family and community are entitled to the protection of health, and the state is responsible arrange to be metright to a healthy life for its residents. Health developmentis directedat health centers Sidomulyo Kecamatan Tampan the health center closest tot he people. Sidomulyo Puskesmas health centers which are accessible to the surrounding community by providing services needed by the community with affordablepayments, especially for the lowand the economy continues to provide health by improving the quality and quantity of life of healthy people to a better direction. The purpose of this study was to determine the characteristics of community health centers Sidomulyo visitor and to know the role of Puskesmas Sidomulyo In Public Health Services in the Kecamatan Tampan Pekanbaru. Respondents in this study were the visitors Sidomulyo health center consisting of 8 respondents. The approach usedin this study is a qualitative research deskriptif research. The process of collecting datausing interviews, observation and documentation. The technique used for retrieval of the respondents was purposive sampling. The results showedthat there areseveral factors the role of health centersin providing health services to the community that is the factor procedure Sidomulyo service, turnaround time, cost of service, service products, Infrastructures, and acompetence officer service providers. The role of health centersin providing health services to the community has been running as well asit should. Puskesmasas ahealth care provider first and closest to the public good with the cooperation between doctors and nurses care workers who work with the regulations set. Puskesmas Sidomulyo provide convenience for the low economic communities with low costby makinglow-cost programssuch asa health card anda letteruni formlypoor.Keywords: The role ofhealth centers,Care, Public Health